I'd Like You to Know - World Bank (Washington, DC, 2015)
This report contains powerful stories, supported by data, of how World Bank Group projects have affected and transformed lives across East Asia and Pacific. There are also photographs that put a face on development statistics. The East Asia and Pacific region is home to more than two billion people. They live in more than 20 different countries; they speak more than 3,000 languages; they are farmers and fishermen, business men and women, students, workers, nomadic herders, all showing that a little can go a long way. They are improving their own lives with a little help from the World Bank Group, their own country and other development partners in the form of investments in the basics of daily life like water, electricity and health care; a small grant, a community-driven development program; business initiatives that cut bureaucratic red tape; scholarships that enable disadvantaged students to skill up for the future; and initiatives to protect the environment and tackle climate change. This dynamic region has experienced remarkable growth and prosperity, with extreme poverty falling faster than in any other region. However, there are still more than 340 million people across the region living on just $2 a day. This report conveys stories demonstrating how these people are changing that statistic.